Permutation entropy applied to the characterization of the clinical evolution of epileptic patients under pharmacological treatment - Mateos, Diego (2014)
Fil: Mateos, Diego. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.